Photoresponse of Schottky-barrier detector under strong IR laser excitation - Asmontas, S.; Seliuta, D.; Sirmulis, E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Peculiarities of the photovoltaic effect in Ti/n-Si Schottky contact have been studied experimentally under infrared (IR) laser excitation at wavelengths 2.79, 3, 5, 7 and 10.6 mm. We demonstrate that strong laser excitation gives rise to the photovoltage even if an incident photon energy is lower than Schottky barrier height. In this case the photovoltage as a function of light intensity follows a power-law dependence with the power greater than unity (2...6). The results are interpreted from the viewpoint of electron emission over the potential barrier due to multiphoton or multistep light absorption at the metal-semiconductor interface.